ANALISIS FAKTOR REPUTASI AUDITOR, DISCLOSURE, DAN AUDIT CLIENT TENURE TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG ADA DI INDONESIA - Widy Hastuty HS; An Suci Azzahra (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Some cases of manipulation of financial data that have occurred in several large companies cause the public accounting profession to be criticized. The role of the auditor in the company is quite large, not only examining the auditee’s financial statements or detecting fraud, but also assessing a company's ability to maintain business continuity. If the auditor finds doubts about the continuity of the business of the company being audited, the auditor should provide a going concern opinion (modified opinion). Besides disclosure of financial statements is also very important for the auditor because it relates to the acceptance of going concern audit opinion on the company. Likewise with the client tenure audit which is the period of engagement between the KAP and the same auditee, where the anxiety of losing a large amount of fee will cause doubts for the auditor to express his going concern audit opinion. Thus the auditor's independence will be affected by the length of the engagement entered into by the KAP with the same auditee. So, research conducted research on the analysis of auditor reputation, disclosure, and client tenure audit factor on going concern audit opinion in manufacturing companies in Indonesia was conducted aimed at analyzing how much influence the auditor, disclosure, and audit client tenure reputation on going audit opinion concern. The research sample was conducted on manufacturing companies in Indonesia and listed on the Indonesia Stock Exchange using purposive sampling method. Logistic regression analysis is used as a data analysis and hypothesis testing technique. The results showed evidence that the auditor's reputation had no significant effect on going concern audit opinion. Disclosure has a positive and significant effect on going concern audit opinion. Client tenure audit has no significant effect on going concern audit opinion. The auditor's reputation, disclosure, and client tenure audit did not significantly influence the going concern audit opinion.